Novel HYDIN variants associated with male infertility in two Chinese families - Yu, Hui; Shi, Xiao; Shao, Zhongmei; Geng, Hao; Guo, Senzhao; Li, Kuokuo; Gu, Meng; Xu, Chuan; Gao, Yang; Tan, Qing; Duan, Zongliu; Wu, Huan; et al. (Frontiers in Endocrinology, 2023)
High-throughput sequencing techniques have identified numerous variants in genes responsible for asthenoteratozoospermia; however, its etiology still needs to be studied. In this study, we performed whole-exome sequencing on samples from 375 patients with asthenoteratozoospermia and identified two HYDIN compound heterozygous variants, a primary ciliary dyskinesia (PCD)-associated gene, in two unrelated subjects. Patient AY078 had novel compound heterozygous splice variants (c.5969-2A>G, c.6316+1G>A), altering the consensus splice acceptor site of HYDIN. He was diagnosed with male infertility and PCD, presenting with decreased sperm progressive motility and morphological abnormalities, and bronchial dilatation in the inferior lobe. Compared to the fertile control, HYDIN levels, acrosome and centrosome markers (ACTL7A, ACROSIN, PLCζ1, and Centrin1), and flagella components (TOMM20, SEPT4, SPEF2, SPAG6, and RSPHs) were significantly reduced in HYDIN-deficient patients. Using intracytoplasmic sperm injection (ICSI), the patient successfully achieved clinical pregnancy. AY079 had deleterious compound heterozygous missense variants, c.9507C>G (p. Asn3169Lys) and c.14081G>A (p. Arg4694His), presenting with infertility; however, semen samples and PCD examination were unavailable. Our findings provide the first evidence that the loss of HYDIN function causes asthenoteratozoospermia presenting with various defects in the flagella structure and the disassembly of the acrosome and neck. Additionally, ICSI could rescue this failure of insemination caused by immobile and malformed sperm induced by HYDIN deficiency.